Pengaruh Penerapan Virtual Reality (VR) untuk Mengenalkan Bangun Datar pada Siswa Kelas IV SD - Rusminati, Susi Hermin; Ladyawati, Erlin (JPPSD: Jurnal Pendidikan dan Pembelajaran Sekolah Dasar, 2025)
This study aims to explore the impact of applying Virtual Reality (VR) technology in teaching flat shapes to fourth-grade elementary school students. Using a quantitative experimental approach, two groups of students were compared: the experimental group using VR and the control group using conventional teaching methods. The results showed that the experimental group experienced a significant improvement in material understanding, with an average score increase of 26.86 points (31.7%), compared to the control group's 13.34 points (18.56%). Moreover, 85% of students in the experimental group felt more motivated, and 90% felt more engaged in the learning process. Observations also indicated that students were more active in asking questions and discussing when using VR. The paired t-test results showed strong significance (p = 0.000), indicating that VR effectively enhances students' geometric understanding. It can be concluded that the application of VR is an innovative solution in mathematics education at the elementary level, especially in introducing the concept of flat shapes. Further research is needed to explore the application of VR in broader educational contexts.